1984
DOI: 10.1017/s0021859600041423
|View full text |Cite
|
Sign up to set email alerts
|

Field studies on 14C assimilate fixation and movement in oil-seed rape (B. napus)

Abstract: SummaryThe roles of leaves, stems and reproductive parts in 14CO2 fixation and its subsequent movement in winter oil-seed rape, cultivar Jet Neuf, were investigated in two field experiments carried out on the Wye College Farm. The relative importance of these organs changed with time. At early flowering the leaves were the most important photosynthetic organs (66·8% 14CO2 activity). Midway between flowering and maturity the stems became the major supplier of photosynthates, a role eventually taken over by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 14 publications
(10 reference statements)
2
25
0
1
Order By: Relevance
“…1B-D) at early flowering, but decreased to the lowest on leaf 8 during the early pod-filling stage, according to the growth stage key described by Harper and Berkenkamp (1975). This observation is consistent with findings of other studies in which leaves were reported to be an important sources of photosynthates up to early flower, when stems and pods became more significant exporters of photosynthates (Major et al 1978;Chapman et al 1984).…”
Section: Photosynthetic Ratessupporting
confidence: 90%
See 1 more Smart Citation
“…1B-D) at early flowering, but decreased to the lowest on leaf 8 during the early pod-filling stage, according to the growth stage key described by Harper and Berkenkamp (1975). This observation is consistent with findings of other studies in which leaves were reported to be an important sources of photosynthates up to early flower, when stems and pods became more significant exporters of photosynthates (Major et al 1978;Chapman et al 1984).…”
Section: Photosynthetic Ratessupporting
confidence: 90%
“…Leaves establish the sink potential in terms of structures such as number of pods per plant or number of seeds per pod and as a source of translocated photosynthates during their senescence, but eventually stems and pods become more important sources of photosynthates (Major et al 1978;Chapman et al 1984).…”
Section: Mots Clés: Colza Oléagineux Brassica Napus Photosynthèse mentioning
confidence: 99%
“…The changing importance of different photosynthesizing organs as sources of assimilates for developing seeds was also recognized in field studies with a B. napus winter cultivar in the United Kingdom (Chapman et al 1984). Major sources of assimilates for developing seeds between early flowering and maturity were, in chronological order, upper leaves, stems and finally the pods themselves.…”
Section: Carbon/nitrogen Metabolismmentioning
confidence: 93%
“…Clarke (1978) also found that foliage removal at the flowering stage had a greater impact on seed yield than foliage removal at the end of flowering. Tolerance of defoliation at late flowering and pod filling stages probably occurs because canola plants rely on photosynthates assimilated directly by the stems and pod walls and stored photosynthates for seed filling (Major et al 1978;Chapman et al 1984).…”
Section: Effect Of Defoliation On Grain Yield Yield Components and Omentioning
confidence: 99%